Management of immune-related adverse events under PD-1/PD-L1 inhibitors: Insights from a Moroccan real-world experience - Inès Cherradi; Mohamed Ichou; Mohammed Squalli Houssaini; Nabil Ismaili (Cancer Treatment and Research Communications)
Background: PD-1 and PD-L1 inhibitors, including pembrolizumab and atezolizumab, have improved survival outcomes in several malignancies. However, their use is frequently associated with immune-related adverse events (irAEs), which can pose management challenges, particularly in resource-limited settings like Morocco where real-world data remain scarce. Objective: To characterize the incidence, spectrum, and severity of irAEs among Moroccan patients treated with pembrolizumab or atezolizumab, and to assess management approaches in light of ASCO and ESMO guidelines. Methods: We conducted a retrospective multicenter analysis between January 2018 and July 2024, involving 31 patients receiving Pembrolizumab or Atezolizumab. Clinical data were collected from patient records and assessed according to the Common Terminology Criteria for Adverse Events (CTCAE) v5.0. Results: Among the 31 patients included, 13 (41.9%) developed at least one immune-related adverse event (irAE), for a total of 15 events. The majority of irAEs were endocrine (16.1%), pulmonary (12.5%), cutaneous (12.5%), and gastrointestinal (6.5%). Most toxicities were grade 1-2, while 2 patients developed severe grade 3 pneumonitis and colitis, requiring hospitalization. Management was based primarily on corticosteroid therapy and supportive care. Importantly, irAEs led to temporary treatment interruption in 5 patients (16.1%) and definitive discontinuation in 2 patients (6.5%). Most patients achieved favorable clinical improvement following appropriate irAE management. Conclusion: Early recognition and management of irAEs are essential to minimize complications and optimize outcomes. This study highlights the need for standardized protocols and enhanced monitoring in the Moroccan context.